Implementation of IoT in Smart City Management to Improve Energy Efficiency - Muhammad Bitrayoga; Evan Haviana; Amat Suroso; Tanwir; Sri Widiastuti (Universitas Muhammadiyah Palu, 2025)
The rapid growth of urbanization in Palembang, South Sumatra Province, poses challenges in the management of energy resources and the environment. This study aims to evaluate the application of Internet of Things (IoT) in the E-Cleanness City Information and Management System program as a solution in improving energy efficiency and smart city operations. Mixed research methods were used, combining quantitative and qualitative analysis to obtain a comprehensive picture of the impact of IoT implementation. The results showed a 10% decrease in energy consumption and a 15% increase in operational efficiency after IoT implementation. The main factors contributing to the efficiency improvement include optimization of waste collection routes, reduction in the number of operational vehicles, and improved response times. In addition, user and system manager satisfaction surveys indicated high levels of satisfaction, indicating positive acceptance of the technology. The social and economic benefits include reduced operational costs, improved quality of life, creation of new jobs, and increased environmental awareness. However, challenges such as limited technological infrastructure, the need for further training, complex system integration, and data security and privacy issues need to be addressed to optimize IoT implementation. This research recommends infrastructure development, intensive training programs, and implementation of strong data security protocols as strategic steps to support the sustainability of smart city management in Palembang. The findings are expected to serve as a reference for the development of similar policies in other cities in Indonesia in an effort to achieve energy efficiency and environmental sustainability through IoT technology.